A biofoundry workflow for the identification of genetic determinants of microbial growth inhibition. Issue 1 (28th January 2021) - Moffat, Alaster D; Elliston, Adam; Patron, Nicola J; Truman, Andrew W; Carrasco Lopez, Jose A
Abstract: Biofoundries integrate high-throughput software and hardware platforms with synthetic biology approaches to enable the design, execution and analyses of large-scale experiments. The unique and powerful combination of laboratory infrastructure and expertise in molecular biology and automation programming, provide flexible resources for a wide range of workflows and research areas. Here, we demonstrate the applicability of biofoundries to molecular microbiology, describing the development and application of automated workflows to identify the genetic basis of growth inhibition of the plant pathogen Streptomyces scabies by a Pseudomonas strain isolated from a potato field . Combining transposon mutagenesis with automated high-throughput antagonistic assays, the workflow accelerated the screening of 2880 mutants to correlate growth inhibition with a biosynthetic gene cluster within 2 weeks.